The fading social trust capital due to cybercrime in e-commerce transactions in Indonesia: The perspective of the electronic information and transaction law - Farida, Any; Dimyati, Khudzaifah; Absori; Wardiono, Kelik; Budiono, Arief (Edelweiss Applied Science and Technology, 2024)
Trade through electronic systems (e-commerce) is a prominent innovation of this current era. The growth of e-commerce in Indonesia is the highest in the world. Even so, there are threats to security in e-commerce due to cybercrimes, especially system interference. This leads to society’s fading trust to e-commerce businesses as a social capital. The Indonesian government has carried out efforts to prevent and handle cybercrimes through stipulations of the Law on Electronic Information and Transaction. Unfortunately, cybercrimes, especially disturbances to the electronic system, still rampantly happen Therefore, this research focuses on how far the Indonesian Law on Electronic Information and Transaction can reach that cybercrime. This was normative legal research which was a form of doctrinal legal research. It employed a data searching method in the form of library research, i.e., studying primary and secondary legal sources and analyzing them using the descriptive qualitative method with deductive logic. Results of this research showed that the Indonesian Law on Electronic Information and Transaction which keeps on experiencing amendments has not reached cybercrimes, especially crimes related to disturbances to the electronic system (system interference). It is not yet effective in guaranteeing the security of e-commerce transactions, leading to the fading of trust as a social capital. The amendment of the Law on Electronic Information and Transaction must be followed with the amendment of its implementing laws. Society must also be introduced to the importance of the Indonesian Law on Electronic Information and Transaction through massive and intensive education programs.